Legal Protection for Consumers of Health Services by Dentists in Indonesia - Dandy Saputro; Rosita Candrakirana (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The purpose of this study was to analyze legal protection for users of health services managed by dentists. Data for this letter were collected through literature review and interviews, followed by descriptive analysis as legal material. The description of the data received in the letter was written and arranged systematically in the form of a sentence description whose meaning is understood as a statement or conclusion. The investigation revealed that the dentist was involved in activities that did not comply with the laws and regulations applicable to dental practice. This caused the victim to suffer losses. The state, which is responsible for supervision and regulation, did not provide guidance or supervision over the work of dental technicians. The dentist committed a violation in providing dental services outside his authority and had a valid dental practice permit from the government as stipulated in the Regulation of the Minister of Health Number 39 of 2014 (Regulation on the Development, Supervision, and Licensing of Dental Practice); The author recommends that the central government work together with local governments to conduct regular and continuous supervision of dental clinic locations and provide training to dentists so that they do not become victims of dental clinics.